2018
DOI: 10.3390/socsci7100176
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Perceived Socio-Economic Impacts of Hosting Large-Scale Sport Tourism Events

Abstract: Large-scale sport events help attract a wide range of attendees, resulting in various implications for the host community. This paper is concerned with understanding the legacy of the 13th EHF European Handball Championship, held in Croatia in January 2018, by assessing the event’s economic and social benefits and costs. Drawing on the Social Exchange Theory, it also examines if any significant differences exist between host city residents and non-host city residents regarding their perceived impacts of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 71 publications
3
57
1
Order By: Relevance
“…Finally, the means of all items within the decline in terrorist threats factor are low, suggesting that this study did not establish that risks of terrorism would be reduced in the eyes of residents. This corresponds with previous findings that local residents did not perceive a significant increase in the risk of terrorist attacks during and after sporting events [29,40,63] although opposite findings also exist [30]. Therefore, the fact that event cancellation will not change the perception of terrorist threats seems to be true.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, the means of all items within the decline in terrorist threats factor are low, suggesting that this study did not establish that risks of terrorism would be reduced in the eyes of residents. This corresponds with previous findings that local residents did not perceive a significant increase in the risk of terrorist attacks during and after sporting events [29,40,63] although opposite findings also exist [30]. Therefore, the fact that event cancellation will not change the perception of terrorist threats seems to be true.…”
Section: Discussionsupporting
confidence: 91%
“…It seems that the local residents' perceived impacts related to community visibility and image deterioration and knowledge and entertainment diminution are more substantial than economic impacts and impacts related to community deconsolidation. While previous studies recognized improved image and greater visibility of the hosting community in the worldwide media as the most significant positive impacts [37,[62][63][64], the opposite result found in this study, that the local residents' perceived image and visibility of the hosting community were decreased due to event cancellation, is not a surprise. Similarly, the high mean scores of items within the factor Knowledge and entertainment diminution are consistent with Kim et al [29], who found knowledge and entertainment opportunities (of held sporting events) as being very important for hosting communities.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although the time frame in this particular study included a prepandemic period, the study reported results from a sample of 12 years with information before and after the big financial and economic crises in 2008 and 2009. Moreover, this study contributed to the recent body of knowledge about wider positive socio-economic impacts of sport tourism events which will be ultimately significant after the current crisis [20]. In order to maximize the positive impacts of running events after crisis events, planners are advised to adopt the adequate participants segmentation as argued by the group of authors [64].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the event impact studies are focused on economic impact, even though there were significant efforts made to assess the social impact [17][18][19][20][21][22][23][24] and environmental impact [25,26] of sports events. More recently, we are witnessing a growing number of studies estimating the perception of local residents towards the event ( [20,21,27,28], p. 1), [29,30], yet some of them come with conflicting conclusions. This could be due to the fact that the resident's perception can change over time, which is why this type of studies is often avoided by researchers [31].…”
Section: The Impact Of Sport Eventsmentioning
confidence: 99%